Production, purification and characterization of cholesterol oxidase from a newly isolated streptomyces sp. - Niwas, Ram; Singh, Vineeta; Singh, Rajbir; Tripathi, Divya; Tripathi, C. K. M. (World Journal of Microbiology & Biotechnology, 2013)
Cholesterol oxidase production (COD) by a new isolate characterized as Streptomyces sp. was studied in different production media and fermentation conditions. Individual supplementation of 1 % maltose, lactose, sucrose, peptone, soybean meal and yeast extract enhanced COD production by 80-110 % in comparison to the basal production medium (2.4 U/ml). Supplementation of 0.05 % cholesterol (inducer) enhanced COD production by 150 %. COD was purified 14.3-fold and its molecular weight was found to be 62 kDa. V-max (21.93 mu M/min mg) and substrate affinity K-m (101.3 mu M) suggested high affinity of the COD for cholesterol. In presence of Ba2+ and Hg2+ the enzyme activity was inhibited while Cu2+ enhanced the activity nearly threefold. Relative activity of the enzyme was found maximum in triton X-100 whereas sodium dodecyl sulfate inactivated the enzyme. The enzyme activity was also inhibited by the thiol-reducing reagents like Dithiothreitol and beta-mercaptoethanol. The COD showed moderate stability towards all organic solvents except acetone, benzene and chloroform. The activity increased in presence of isopropanol and ethanol. The enzyme was most active at pH 7 and 37 A degrees C temperature. This organism is not reported to produce COD.
Keywords: Affinity chromatography; Cholesterol oxidase; HPLC; SDS PAGE; Streptomyces sp.

Isolation, characterization and antifungal docking studies of wortmannin isolated from penicillium radicum - Singh, Vineeta; Praveen, Vandana; Tripathi, Divya; Haque, Shafiul; Somvanshi, Pallavi; Katti, S. B.; Tripathi, C. K. M. (Scientific Reports, 2015)
During the search for a potent antifungal drug, a cell-permeable metabolite was isolated from a soil isolate taxonomically identified as Penicillium radicum. The strain was found to be a potent antifungal agent. Production conditions of the active compound were optimized and the active compound was isolated, purified, characterized and identified as a phosphoinositide 3-kinase (PI3K) inhibitor, commonly known as wortmannin (Wtmn). This is very first time we are reporting the production of Wtmn from P. radicum. In addition to its previously discovered anticancer properties, the broad spectrum antifungal property of Wtmn was re-confirmed using various fungal strains. Virtual screening was performed through molecular docking studies against potential antifungal targets, and it was found that Wtmn was predicted to impede the actions of these targets more efficiently than known antifungal compounds such as voriconazole and nikkomycin i.e. 1) mevalonate-5-diphosphate decarboxylase (1FI4), responsible for sterol/isoprenoid biosynthesis; 2) exocyst complex component SEC3 (3A58) where Rho-and phosphoinositide-dependent localization is present and 3) Kre2p/Mnt1p a Golgi alpha1,2-mannosyltransferase (1S4N) involved in the biosynthesis of yeast cell wall glycoproteins). We conclude that Wtmn produced from P. radicum is a promising lead compound which could be potentially used as an efficient antifungal drug in the near future after appropriate structural modifications to reduce toxicity and improve stability.